Activity rating scales in adult muscle disease: What do they actually measure?. Issue 1 (11th January 2014) - Seedat, Farah; James, Meredith K.; Rose, Michael R.
Abstract Introduction: There is a diversity of rating scales that assess function in muscle disease. Definitive knowledge of the content covered by these scales would help in making choices. Methods: We searched for activity rating scales used for muscle disease and assessed their content by linking scale items to the International Classification of Functioning, Disability and Health (ICF) and the muscle regions they cover. Results: Of the 119 scales found, 19 muscle disease–specific and 9 generic scales were prioritized for analysis. These 28 scales contained 457 items, from which 1145 concepts were identified and 160 were unique. Of these concepts, 97.8% could be linked to the ICF, most to the activities and participation domain (68.7%), followed by environmental factors (22.5%) and body functions (6.6%). Global muscle function was assessed most frequently, followed by lower and upper extremity function. Conclusions: This content comparison should allow for a better‐informed choice of activity rating scales for muscle disease. Muscle Nerve50: 14–23, 2014